Emotional reactions in patients after frontal lobe stroke - Stojanović, Zlatan; Vukadinović Stojanović, Sanja (Vojnosanitetski pregled, 2015)
Background/Aim. Emotional reactions have been documented after tumor lesions and the other damages of the brain. The aim of this paper was to examine the correlation between frontal lobe lesions and emotional reactions in patients with stroke. Methods. The research included 118 patients after stroke. Lesion localization was defined on computed axial tomography records, whereas the area and perimeter of lesion were measured by AutoCAD 2004 software. Examinations by means of the Hamilton Rating Scale for Anxiety and Depression (HRSA and HRSD) were carried out 11–40 days after stroke. Statistic data were processed by simple linear/nonlinear regression, Cox’s and the generalized linear model. Results. A higher frequency of emotional reactions, i.e. anxiety, was determined in women after stroke (p = 0.024). A negative correlation between the lesion size and the intensity of anxiety manifestations was determined (Spearman’s r = -0.297; p = 0.001). Anxiety was more frequent in patients with frontal lobe lesions in the dominant hemisphere (interaction: frontal lesion * hand dominant hemisphere, p = 0.017). Also, HRSD score values showed the tendency for lesser decline in case of greater frontal lobe lesions in relation to lesions of other regions of prosencephalon (interaction: frontal lesion * lesion area, p = 0.001). Conclusion. The results of this study indicate the correlation between evolutionary younger structures of the central nervous system and emotional reactions of man. Therefore, it is necessary to undertake proper early psychopharmacotherapy in the vulnerable group of patients.